The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biomedicines9070758
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar and Vaginal Melanomas—The Darker Shades of Gynecological Cancers

Abstract: Melanomas of the skin are poorly circumscribed lesions, very frequently asymptomatic but unfortunately with a continuous growing incidence. In this landscape, one can distinguish melanomas originating in the mucous membranes and located in areas not exposed to the sun, namely the vulvo-vaginal melanomas. By contrast with cutaneous melanomas, the incidence of these types of melanomas is constant, being diagnosed in females in their late sixties. While hairy skin and glabrous skin melanomas of the vulva account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…In general, the female gender appears to be a risk factor for MM, as they are twice as common in women compared to men. In contrast, cutaneous melanoma (CM) distribution is similar between both genders [ 4 ] . Additionally, certain genetic alterations are found to be associated with MM: activating mutations in SF3B1 and KIT, loss of CDKN2A, PTEN or SPRED1, and amplification of CDK4, TERT, KIT, MDM2 or CCND1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the female gender appears to be a risk factor for MM, as they are twice as common in women compared to men. In contrast, cutaneous melanoma (CM) distribution is similar between both genders [ 4 ] . Additionally, certain genetic alterations are found to be associated with MM: activating mutations in SF3B1 and KIT, loss of CDKN2A, PTEN or SPRED1, and amplification of CDK4, TERT, KIT, MDM2 or CCND1.…”
Section: Discussionmentioning
confidence: 99%
“…Gene sequencing of MM helps identify driver mutations and provides therapeutic opportunities for targeted therapy. The most common presenting complaint of vaginal melanomas is genital bleeding, while others include a palpable mass, itching, dyspareunia, yellow genital secretions, and local pain [ 4 ] . The diagnosis of vaginal melanomas includes pathological analysis and IHC of the biopsy sample, imaging to determine extent, and genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment specialty-specific characteristics and outcomes in women with vulvo-vaginal melanoma: A JGOG-JSCS joint study Melanoma of the female genitalia, including the vulva and vagina, represents a rare type of malignancy that is associated with poor survival outcomes. [1][2][3] Due to the rarity, vulvo-vaginal melanomas have been relatively understudied and treatment often includes overlap between the dermatologists, representing expertise in melanoma, and the gynecologists who possess the expertise in female genital tract malignancy.…”
mentioning
confidence: 99%
“…While various studies have reported prognostic factors for vulvovaginal melanomas, [1][2][3][4][5] the prognostic effect of treating specialty for vulvo-vaginal melanomas (dermatologists vs. gynecologists) has not been previously examined. The objective of the current study was to compare characteristics and outcomes of women with vulvo-vaginal melanoma based on the specialty of the physician guiding treatment.…”
mentioning
confidence: 99%